Upaya Mengembangkan Kecerdasan Musikal Melalui Permainan Persepsi Bentuk Musikal Pada Anak Kelomok B di TK Pertiwi Tanjung Juwiring Klaten Tahun Pelajaran 2012/2013 - Syafe’i, Muhammad (?ALI?A, 2018)
This study aims to develop musical intelligence group B children inTK Pertiwi Desa Tanjung District Juwiring Klaten Lesson Year 2012/2013through the game of musical form perception. This research is a classroomaction research (PTK). In this research, the students are group B in TK PertiwiDesa Tanjung Kecamatan Juwiring Klaten District Lessons Year 2012/2013as many as 18 children, consist of 12 men and 6 women. This research wasconducted in two cycles each cycle consisting of planning stage, action stage,observation, reflection.Children's musical intelligence data was collected through observationmethods, and documentation. Data analysis technique used is descriptivequalitative with interactive analysis consisting of data reduction, datapresentation, and conclusion of analysis result. Research results before theimplementation of the cycle obtained results of 41.9%, the first cycle reached56.4%, and the second cycle reached 80.1%. based on research that has beendone can be concluded that through the game perception of musical form canimprove the musical intelligence of children in kindergarten Pertiwi VillageCape District Juwiring Klaten Lesson Year 2012/2013.